Financial condition and audit procedure - Square Toiletries Ltd. (STL) - Sinthia, Sanjida Afrin (BRAC University, 2015)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2015.